2018
DOI: 10.1007/s11103-018-0744-7
|View full text |Cite
|
Sign up to set email alerts
|

High-level expression of the HIV entry inhibitor griffithsin from the plastid genome and retention of biological activity in dried tobacco leaves

Abstract: Key messageThe potent anti-HIV microbicide griffithsin was expressed to high levels in tobacco chloroplasts, enabling efficient purification from both fresh and dried biomass, thus providing storable material for inexpensive production and scale-up on demand.AbstractThe global HIV epidemic continues to grow, with 1.8 million new infections occurring per year. In the absence of a cure and an AIDS vaccine, there is a pressing need to prevent new infections in order to curb the disease. Topical microbicides that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 58 publications
0
25
0
Order By: Relevance
“…Another inspirational study was presented by Matthijs Hoelscher (Max Planck Institute of Molecular Plant Physiology, Potsdam, Germany), who was awarded the best oral presentation prize by his peers. He discussed how the protein synthesis machinery of Nicotiana tabacum can be used to efficiently produce griffithsin in plasmids (Hoelscher et al ., ). Since griffithsin functions as an anti‐HIV microbicide, his research helps develop cost‐efficient and large‐scale production of HIV medication.…”
Section: The Appreciation Of Applied Researchmentioning
confidence: 97%
“…Another inspirational study was presented by Matthijs Hoelscher (Max Planck Institute of Molecular Plant Physiology, Potsdam, Germany), who was awarded the best oral presentation prize by his peers. He discussed how the protein synthesis machinery of Nicotiana tabacum can be used to efficiently produce griffithsin in plasmids (Hoelscher et al ., ). Since griffithsin functions as an anti‐HIV microbicide, his research helps develop cost‐efficient and large‐scale production of HIV medication.…”
Section: The Appreciation Of Applied Researchmentioning
confidence: 97%
“…This binding activity to surface glycoproteins blocks the virus from entering into human cells. In the case of HIV, GRFT binds to the surface glycoprotein gp120 and blocks the virus from binding to its receptors on host cells (Hoelscher et al, 2018). GRFT has shown to be a very effective anti-viral against HIV, and a previous study has shown that manufacturing GRFT at an industrial scale is feasible and easily scalable (Fuqua et al, 2015a,b).…”
Section: Introductionmentioning
confidence: 99%
“…Plants have proven to be particularly advantageous for expressing GRFT because of high yields of properly folded, active protein. In addition, plants are typically regarded as a safe production platform for biopharmaceuticals (Hoelscher et al, 2018). Therefore, current research has focused on how to separate manufacturing and processing from plant growth and how to optimize outdoor plant-based pharmaceutical manufacturing methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of researchers is working on this concept for more than twenty years, vast research is performed on hepatitis B vaccine also the variety of plant species have been used to express antigen (like banana as can be consumed raw, is a leading candidate for edible vaccines, at a same time it is all time favorite of children. Potato is drought resistant and largely cultivated likewise, strawberry, apple, maize, tomato [30] are studied in number of beneficial researches for edible vaccine development most prominent studies include the development of plant-based vaccines for HCV, HBV [31] Influenza vaccines [32] respiratory syndrome virus and HIV vaccines [33]. Parenteral delivery of plant-based vaccines is well known and verified requires purification before delivery of antigens [34].…”
Section: Introductionmentioning
confidence: 99%